Konsep Ikhlas Perspektif Al Ghazali dan Relevansinya terhadap Pendidikan Agama Islam - Lathiefatul Aghniyah; Mahmud Arif (Al-Kindi, 2025)
This study examines the concept of sincerity according to Imam Al-Ghazali and its relevance to Islamic religious education. Sincerity is understood as the purification of intentions from all goals other than Allah SWT, while riya' is its opposite which damages the value of good deeds and has a negative impact on the purity of the heart and one's psychological health. This study uses a literature study method by examining Al-Ghazali's work in Ihya' 'Ulumuddin as well as supporting research on tazkiyatun-nafs, moral development, and Islamic educational practices. The results of the analysis show that Al-Ghazali divides sincerity into two forms, namely sincerity in good deeds and sincerity in expecting rewards, both of which shape the inner orientation of a believer. The relevance of the concept of sincerity in Islamic religious education is evident in the importance of character formation, sincerity in learning, and teacher role models. Amidst the culture of image and worldly orientation in modern education, the value of sincerity becomes a spiritual foundation that directs students towards intrinsic motivation and moral behavior. This finding confirms that the concept of sincerity according to Al-Ghazali is very important for building Islamic education that is oriented towards purifying the soul, sincerity of worship, and the formation of civilized human beings. Keywords: Ikhlas, Imam Al-Ghazali, Islamic Religious Education, Character Education